As crianças protagonistas dos contos de fadas dos Irmãos Grimm - Costa, Ana Beatriz Farinaccio da [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The origins of the fairy tales are lost in the past but these tales are, even today, great teaching instruments because they relate to language development, creativity, social relations, and especially with the internalization of values and behavior patterns. According to Bettelheim (1980), fairy tales assure the children that the difficulties can be overcome, no matter how insignificant they feel. In this sense, these tales are power tools. We understand that fairy tales - and their characters - have the power to influence their readers/listeners. Therefore, this study considered four fairy tales in which the protagonists are children and remain as children all though the narratives: Little Red Riding Hood, Hansel and Gretel Snow White and Rose Red and Thumbling, from Grimm Tales, translated into Portuguese by David Jardim Junior and published in 2008 by Itatiaia. We sought investigate how the children characters of these stories act, leveraging a reflection grounded on the image of children that emerge from the selected tales - images that have been registered in the first decades of the nineteenth century by the Brothers Grimm in their Children's and Household Tales - enabling the identification of the kinds of behavior that they perform and the values they embody, thus contributing to a better understanding of the models that these characters offer to the twenty-first century's children. Our research has a qualitative approach of bibliographic nature, mainly grounded in the ideas of Bettelheim (1980) and Ariès (1981). We found that there is a shortage of studies on the tales collected/maintained by the Brothers Grimm, although these stories have become classics of universal children's literature and continue, cradling the imagination of Western children in the twenty-first century. We also verified that there are very few studies exploring the representation of children in fairy tales and children's literature...

Os contos de fadas, cujas origens se perderam no tempo são, ainda hoje, grandes instrumentos pedagógicos porque se relacionam ao desenvolvimento da linguagem, da criatividade, das relações sociais e, principalmente, com a interiorização de valores e modelos de comportamento. Segundo Bettelheim (1980), os contos de fadas garantem à criança que as dificuldades podem ser vencidas, por mais insignificante que se sinta quem deseja vencê-las. Neste sentido, esses contos constituem-se em instrumentos de poder. Entendendo que as histórias - e seus personagens - têm o poder de influenciar seus leitores/ouvintes, este estudo considerou quatro contos em que as personagens protagonistas são crianças e permanecem como crianças na totalidade das narrativas: Chapeuzinho Vermelho, João e Maria, Branca de Neve e Rosa Vermelha e O Polegar, narrativas da obra Contos de Grimm, traduzida por David Jardim Júnior, publicada em 2008 pela editora Itatiaia. Buscamos investigar como agem as personagens crianças desses contos, alavancando uma reflexão alicerçada na imagem das crianças que afloram dos contos - imagens que foram registradas nas primeiras décadas do século XIX pelos irmãos Grimm em seus Contos de Fadas para o Lar e as Crianças -, possibilitando a identificação dos tipos de comportamento que têm e os valores que incorporam, contribuindo, assim, para um maior conhecimento sobre os modelos que essas personagens oferecem às crianças do século XXI. Nossa pesquisa é bibliográfica, de caráter qualitativo, fundamentada nas ideias de Bettelheim (1980) e Ariès (1981), prioritariamente. Verificamos que há uma escassez de estudos sobre os contos coletados/conservados pelos irmãos Grimm, ainda que as histórias tenham se tornado clássicos da literatura infantil universal e continuem, neste século XXI, embalando a imaginação das crianças ocidentais. Verificamos, também que há poucos estudos que...
Keywords: Grimm, Jacob 1785-1863; Grimm, Wilhelm 1786-1859; Educação pre-escolar; Contos de fadas; Literatura infantojuvenil; Educação de crianças; Crianças - Conduta